Assessing the effect of the joint governance of transboundary pollution on water quality: Evidence from China - Jing, Shouwu; Liao, Liping; Du, Minzhe; Shi, Enyi (Frontiers in Environmental Science, 2022)
The joint governance of transboundary river pollution is an important means to resolve disputes between upstream and downstream, to achieve regional coordinated development and water environment governance. In this paper, dissolved oxygen, chemical oxygen demand and ammonia nitrogen are used to measure water quality. Regarding the joint governance of transboundary water pollution as a quasi-natural experiment, this paper employs a difference-in-differences model of causal judgment to assess the effect of the policy on transboundary water quality based on the water quality monitoring week data from 2004 to 2016 in China. The results show that compared with non-trans-provincial rivers, the joint governance of water pollution at the provincial boundary could significantly promote the rise of dissolved oxygen, while reducing the chemical oxygen demand and ammonia nitrogen emissions. Additionally, the long-term dynamics based on the dynamic trend suggests that the implementation of this policy has fluctuations in the improvement of dissolved oxygen, but has a strong continuous effect on the reduction of chemical oxygen demand and ammonia nitrogen. These results stand up to robustness tests. Moreover, the green promotion pressure of officials and stakeholder supervision are important influence mechanisms of transboundary joint pollution control on improving transboundary water quality. An important implication is to provide a long-term way for collaborative water pollution control and solving transboundary water pollution disputes.